(untitled) (Malaysian Management Journal, 2024)
The study sought to ascertain corporate governance reforms that foster sustenance of the SOEs in Zimbabwe and how such reforms can be implemented. This study has used a mixed-methods technique and a pragmatist philosophy. A cross-sectional survey design was employed, whereby structured questionnaires and interviews were used to collect data. Top and middle management, board members, board chairpersons, and CEOs of Zimbabwe’s SOEs made up the target population. For quantitative data, a sample size of 351 people was obtained using the sample process created by Krejcie and Morgan (1970). Interviews were done with sixteen (16) people until saturation was achieved. Stratified random sampling was used in the study to choose respondents for the quantitative data collection. To choose interview subjects for the qualitative data, purposeful sampling was applied. The quantitative and qualitative data were analyzed using SPSS version 23 and NVivo version 12, respectively. According to the study, the primary corporate governance reforms for the survival of the SOEs in Zimbabwe included the following: open nomination processes for the SOEs; removal and resignation of directors who did not comply with best corporate governance practices; limitations on board member compensation; and changes to the executive directors’ terms of service. This research has shown that best corporate governance practices in the SOEs are brought about by reforming the Board Appointments Board (RAB). In order to ensure that corporate governance reforms are implemented effectively, the present study has suggested that term limits, with a maximum of ten (10) years, in Chief Executive Officer Employment contracts be strictly enforced.